A companion to George Eliot - Anderson, Amanda, 1960-; Shaw, Harry E., 1946- (Chichester, West Sussex, UK : John Wiley & Sons Limited, 2013)
This collection offers students and scholars of Eliot's work a timely critical reappraisal of her corpus, including her poetry and non-fiction, reflecting the latest developments in literary criticism. It features innovative analysis exploring the relation between Eliot's Victorian intellectual sensibilities and those of our own era. A comprehensive collection of essays written by leading Eliot scholars Offers a contemporary reappraisals of Eliot's work reflecting a broad range of current academic interests, including religion, science, ethics, politics, and aesthetics.
pt. 1. Imaginative form and literacy context -- pt. 2. Works -- pt. 3. Life and reception -- pt. 4. Eliot in her time and ours : intellectual and cultural contexts.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Eliot, George, -- 1819-1880 -- Criticism and interpretation; Eliot, George, -- 1819-1880; Eliot, George, -- 1819-1880.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Electronic books; Criticism, interpretation, etc